Media, Islam, dan Politik Identitas dalam “Bulan Terbelah di Langit Amerika” - Aziz, Abdul Muhaiminul; Mutqiyyah, Rizqi (Jurnal Komunikasi Islam, 2020)
Western media is considered to have an important role war in constructing a negative image of Islam throughout the world, especially after the 9/11 WTC attacks. It inspired the emergence of various popular cultural products, especially in several Muslim-populated countries, which carried out a counter-culture to this reality. This study discusses how the construction of Islam within Western media in the novel Bulan Terbelah Di Langit Amerika. This research used a qualitative method utilising a media text analysis approach. The results showed that the media played an important role in constructing the identity of Islam, as the world enemy, was a media marketing strategy to increase product circulation. This negative view of Islam may be due to the absence of comprehensive information about Islam.